Pemahaman Masyarakat Tentang Zakat Digital di Kecamatan Lembah Melintang Kabupaten Pasaman Barat - M Yarham (Journal of Islamic Social Finance Management, 2026)
This study aims to determine the community's understanding of digital zakat in Lembah Melintang District, West Pasaman Regency, and the factors influencing the use of digital zakat among the community. This research employed a qualitative research method with a descriptive approach. Data were collected through observation, interviews, and documentation involving community members, religious leaders, village officials, and several informants related to the use of digital zakat. The results showed that the people of Lembah Melintang District were familiar with digital zakat through mobile banking applications, QRIS, social media, and information from zakat institutions. However, the community's understanding of digital zakat is still at a basic level and has not been fully optimal. Most people still prefer conventional zakat payment methods through mosques, mushalla, or directly to mustahik because they are considered clearer and more trustworthy. Factors influencing public understanding of digital zakat include education level, digital literacy, age, community culture, trust in zakat management institutions, and the lack of socialization regarding digital zakat. In addition, the community still has concerns regarding the security of digital transactions, such as online fraud and personal data leakage. Therefore, more intensive socialization and education from zakat institutions, the government, and religious leaders are needed to improve public understanding and the use of digital zakat services.